Effect of Aluminium Stress on Germination, Growth and Photosynthetic Pigments of Amaranthus hybridus - Musyimi Mutisya David (Journal of Biodiversity and Biotechnology, 2023)
Amaranthus hybridus is widely distributed and used as a food plant in many parts of the world. Aluminium toxicity in the soil is one environmental stress that limits crop growth and production in acid soils. However, the level of aluminium stress tolerance depends on the plant species or genotype.  A study was conducted at Maseno University, Kenya on the effects of aluminium stress on germination, growth and leaf photosynthetic pigments of  Amaranthus hybridus seedlings. Ten uniform seeds of Amaranthus hybridus weretreated in sodium hypochlorite solution and were placed on dried petri dishes lined with Whatsman No. 1 filter papers.  Filter papers were then moistened with 5ml of  nutrient solution containing either 0 mM (distilled water) or (2, 4, 6, 8 and 10 mM) (Al toxicity) AlCl3·6H2O replicated three times. The germination was assessed for five days to ascertain the number of seeds that germinated over time.  Five litre pots were filled with top soil from Maseno University’s garden. Five seeds of Amaranthus hybridus were sown in each of the pots and were irrigated every day with 250 ml of tap water per pot for two weeks. After two weeks the seedlings were thinned to 2 plants per pot and treatments initiated. Seedlings were irrigated daily with nutrient solution containing 0 mM (control – tap water) or (2, 4, 6, 8 and 10 mM) (Al toxicity) AlCl3·6H2O in triplicates arranged in a completely randomized design in a green house. Data on shoot height, leaf area and number of leaves, shoot and root fresh and dry weights, chlorophyll a, chlrophyl b, total chlorophyll and carotenoid contents were determined at the end of the experiment. Data collected was subjected to analysis of variance (ANOVA) and treatment means separated and compared using Least Significance Difference (LSD). Germination percentage of Amaranthus hybridus was significantly reduced by the aluminiumsolution stress as compared to control treatment. Growth and photosynthetic pigments parameters were significantly reduced by the aluminium stress.The results of this study have clearly shown that  Amaranthus hybridus speciesis very sensitive to aluminium toxicity.